Peran Agama Dalam Pembentukan Perilaku Anti-Korupsi - Rus Yandi (STAI Terpadu Yogyakarta, 2021)
The problems faced by the nation are now widespread corrupt behavior, since the beginning of this country independence, this corruption has penetrated all levels of society, both individually and collectively, both private and government agencies, crime continues to increase in number, especially in state institutions, this is based on data. which shows that, Indonesian Corruption Watch (ICW) researcher Wana Alamsyah said, there were 169 cases of corruption during the first semester of 2020. Overcoming corruption practices with a legal approach has not been effective, so with a religious approach, it will be able to form anti-corruption behavior